Nontraditional Forms of Crediting in Agriculture - Žaltauskienė, Nijolė (Ekonomika, 1997)
Lease and commercial crediting are the most popular forms of nontraditional sources of crediting forms in agriculture. Most economists distribute leases for operating and financing and sale leaseback arrangements leases. In accordance with the property law, the leasing may be devoted to usual and redemption lease. In this article we analyzed the organization of commercial crediting and leasing operations and problems with their accounting.